Effectiveness of a 1-day workshop on scientific writing conducted by the Indian journal of rheumatology - Mohit Goyal; Durga Prasanna Misra; Samir Rajadhyaksha; Yogesh Preet Singh; Neha Goyal; Vinod Ravindran (Indian Journal of Rheumatology)
Background: Writing a scientific manuscript is an important skill to acquire for junior doctors considering the mandatory requirement of research publications during post-graduate training and for career advancement in India. Methods: We conducted a one-day workshop on scientific writing and publication at Udaipur in November 2017, comprising both didactic lectures as well as hands-on evaluation of a dummy manuscript, and evaluated structured questionnaires filled pre- and post-workshop. Results: There were 120 attendees, most of whom were junior doctors with little or no prior experience in writing a scientific paper. A significant baseline knowledge deficit regarding the principles and processes of scientific writing (ranging from 20.9% to 77.3% participants for the different questions asked) could be identified before the workshop. This knowledge deficit was significantly improved in most areas as assessed after the workshop. We identified the need to discuss predatory publishing in greater detail in subsequent workshops, as 20.8% of respondents after the workshop professed that they might consider publishing in a predatory journal. As expressed in participant feedback, longer, more-specialized or advanced level workshops on scientific writing in the future could also consider including more details on appropriate statistical presentation and pictorial representation of data as well as longer time spent on hands-on exercises. Conclusion: There remains a need to conduct more scientific writing workshops by national societies and journals all over the country.